Comparação das respostas perceptivas e motivacionais entre diferentes protocolos de treinamento intervalado. - Marin, Douglas Popp (2019)
The general objective of this study was to investigate the perceptual responses to battling rope interval training (BRIT) and to examine the relationship of the affective response with motivational indicators related to exercise adherence. We conducted two studies. In the study 1, 14 young adult physically active volunteers (24 ± 4 years old, 80.5 ± 8.27 kg, 175.4 ± 4.66 cm, BMI 26.2 ± 2.72 kg /m2 and 11.5 ± 4.41% of body fat) performed three BRIT protocols in randomized counterbalance order: P10:30 (12 x 10-s efforts, 30-s recovery); P15:45 (8 x 15-s efforts, 45-s recovery); and P30:90 (4 x 30-s efforts 90-s recovery). All protocols were performed in all-out intensity, with passive recovery, maintaining the density (work to rest ratio) in 1:3. Immediately at the end of each set the affective response (FS), activation (FAS), rating of perceived exertion (RPE) and heart rate (HR) were measured. During recovery period, motivational indicators such as enjoyment, self-efficacy and intention were accessed. There was a significant decline in FS and a progressive increase of FAS, RPE, HR, however, no difference between protocols was observed. Likewise, no significant difference was observed for motivational indicators between protocols. The results indicated that the inverse relationship between FS decline and RPE increment may be moderate to perceived tolerance. Regression analysis revealed that FS response and self-efficacy may predict the intention to repeat BRIT. The effect of FS response on intention was mediated by the self-efficacy perception. In study 2, we investigated wheter self-selected rest interval (RI) could influence perceptual and motivational responses during and after BRIT. Twelve physically active men (22 ± 6 years, 77.2 ± 9.83 kg, 175.4 ± 5.83 cm, BMI 25.1 ± 2.70 kg/m2 and 9.35 ± 4.93 % body fat). Two BRIT protocols were performed: prescribed protocol (P15:45 - identical to study 1) and self-selected protocol (8 x 15-s efforts, self-selected RI). The results showed that there was no difference in the perceptual and motivational responses between protocols. However, the increase in HR during the prescribed protocol was significantly higher than in self-selected RI. Taken together, the results of both study 1 and 2 showed that the manipulation of the working time and RI in BRIT did not influence the perceptual responses during the exercise, particularly when total volume and intensity are equated. In addition, FS can directly and indirectly influence the motivational factors involved in adherence to exercise.